Державне регулювання як інструмент підвищення - Хрип'юк, Вікторія Іванівна (My University, 2021)
Дисертаційна робота присвячена узагальненню й розвитку теоретико-правових, науково-методичних положень, розробці практичних рекомендацій щодо удосконалення державного регулювання харчової промисловості України з метою підвищення її ефективності. У роботі систематизовані ключові теоретико-методичні погляди на роль держави в забезпеченні соціально-економічного розвитку. Досліджено науково-методичні аспекти онтогенезу «державного регулювання» та пов’язаного з ними категоріально-понятійного апарату. Узагальнено теоретичні та методологічні основи державного регулювання харчової промисловості, на підставі чого запропоноване його авторське визначення та сформовано механізм державного регулювання харчової промисловості, що генерує створення підвалин досягнення запрограмованих на державному рівні стратегічними документами структурних зрушень у конкретизованих інститутах харчової промисловості країни. Здійснено ретроспективний аналіз та аналіз сучасного стану розвитку харчової промисловості України. Визначено та систематизовано в ієрархічному порядку інституційні одиниці державного регулювання харчової промисловості, зокрема, підприємницьких структур в нормативній, методичній, інструктивній та науковій площинах. Визначені «сильні» та «слабкі» регуляторні важелі, що формують ефективність розвитку харчової промисловості України. Обґрунтовано перспективні напрями удосконалення державного регулювання розвитку харчової промисловості України та запропоновано набір інструментів в межах визначених двох напрямків, націлених на підтримку розвитку виробництва з більш глибоким технологічним процесом продукції з високою часткою доданої вартості та сприяння збільшення експорту такої продукції як основного інструмента щодо підвищення ефективності розвитку харчової промисловості. The dissertation is devoted to summarizing and developing the theoretical-legal and scientific-methodological provisions, as well as the development of practical recommendations with regards to improving the state regulation of Ukraine’s food industry in order to increase its efficiency. The paper systematizes the key theoretical and methodological views on the state's role in ensuring socio-economic development. Based on this, it has been determined that in world literature in general two opposite points of view regarding the necessity of state-regulated economic processes are considered. However, under current conditions of the market economy, state regulation acquires a special status, as state influence on the activities of economic entities should interact as much as possible with market self-regulation, supporting and stimulating, rather than replacing it. Furthermore, the scientific and methodological aspects of the ontogenesis of “state regulation” have been studied, as well as the relevant categorical and conceptual basis. The essence of theoretical approaches to the implementation of state regulation has been examined and the scientific-theoretical ways of defining “state regulation of the food industry” have been summarized. The mechanism for state regulation of the food industry has been formed, which generates the framework for the achievement of structural changes, initiated at the state level by strategic documents in specific institutions of the country’s food industry. A retrospective analysis, as well as the analysis of the current state of Ukraine’s food industry, has been carried out. Based on this it has been determined that for a long time the food industry has been one of the most strategically important sectors of the national economy. The conceptual provisions of using the nomenclature-product approach in state statistical reporting on the Ukrainian food industry’s development have been substantiated which, unlike others, details the sector breakdown. The above allows to determine the development of individual sectors of the food industry through quantitative and qualitative indicators of progress of the corresponding nomenclature-product composition, as well as to decrease the risks of distorting the objective estimates of transformational changes in the industry and its subsectors. The institutional and normative support of state regulation of the Ukrainian food industry has been analyzed, on the basis of which the institutional units of regulation, namely the business structures in the normative, methodical, instructive, and scientific planes, have been arranged in hierarchical order. The methodological approach to evaluating the state regulation of the food industry has been improved which, in contrast to the existing ones, include a system of quantitative and qualitative indicators, grouped in accordance with the criteria of assessment, namely administrative-political, economic, social, and investment-innovative, as well as providing for the formation of a general integrated indicator. This allows for the objective evaluation of state-regulated development and the efficiency of the food industry, as well as defining the means of its improvement. The main issues and obstacles in the development of the food industry have been laid out, along with ranking the industries they most concern. Simultaneously, the main prospects and advantages of their advancement have been established, based on the methodological approaches to the systemic analysis of the food industry’s development. Moreover, the strengths and weaknesses of Ukraine’s food industry, as well as the opportunities and potential threats in the event of the intensification of state action have been systematized using the SWOT-analysis method. The prospective methods of improving state regulation of Ukraine’s food industry have been affirmed and a set of tools within the two established directions, aimed at advancing the development of products with high added value, has been proposed, along with the means of increasing the export of such products. It has been established that the main function of a state, guided by the goal of increasing the efficiency of its food industry, is stimulating the production end export of food products with high added value.
Keywords: харчова промисловість; державне регулювання; додана вартість; експорт; інструменти державного регулювання; food industry; state regulation; added value; export; instruments of state regulation